Descripción de la larva de phyllophaga (phytalus) rufotestacea (moser) (coleoptera: melolonthidae) en Chiapas, México - Ramírez-Salinas, Concepción; Morón, Miguel-Ángel; Castro-Ramírez, Adriana E.; Pacheco-Flores, Cutberto (Instituto de Ecología, A.C., 2009)
The third-instar larva of Phyllophaga (Phytalus) rufotestacea (Moser, 1918) is described and illustrated, based on specimens reared from eggs laid by captive adults collected in San Cristobal de Las Casas, Chiapas, Mexico. Some data on the life cycle and habits are included.